Regional Differences in the Years of Potential Life Lost in the Context of Avoidable Mortality from Cardiovascular Diseases - A. A. Grigorov; T. P. Sabgayda; A. V. Zubko (Здоровье мегаполиса)
Disparities in mortality rates within a country indicate social inequalities in population health across different regions. Initiatives aimed at reducing mortality have shown to effectively decrease preventable deaths and extend the lives of individuals with cardiovascular diseases; therefore, it is relevant to compare regions based on years of potential life lost (YPLL) due to premature preventable mortality.The aim of the study was to compare YPLL for individuals who died from avoidable and unavoidable causes of cardiovascular diseases in Russian regions with different levels of available specialized medical care.The results align with the hypothesis that regions with limited access to specialized medical care show higher rates of YPLL due to preventable cardiovascular disease deaths regardless of the morbidity, i.e., regional differences in mortality rates are highly related to social inequalities. To the greatest extent, premature preventable mortality from cardiovascular diseases is influenced by the availability of cardiology professionals.The majority of cardiovascular deaths were avoidable. On the eve of the COVID-19 pandemic, YPLL were more than 27 years per 1,000 population among men and more than 9 years among women, accounting for 69.2% and 69.8% of total preventable YPLL for men and women, respectively.